(239) The Elaboration Of Research Programs In The Institute (A Background Paper) شرح برامج البحث في المعهد (ورقة معلومات أساسية) - I.H. Abdel-Rahman (معهد التخطيط القومي, 2026)
The memorandum the strategy for developing scientific research programs within the institute. The document explains that the institute initially focused on training to meet the urgent needs of government ministries following the launch of the first national plan. However, the time has come to organize research activity more systematically. The paper reviews the obstacles that research faced at the beginning, such as a shortage of academic staff, preoccupation with administrative matters, and data availability. It emphasizes that the institute is now striving to move from individual or contractual research activities to establishing a comprehensive institutional framework that integrates the specializations of faculty members with the needs of national planning.